Potensi Kandungan Karbon Keragaman Spesies Lamun di Perairan Pesisir Selatan Lombok Timur - I Gusti Ayu Sintia Dewi; Abdul Syukur; I Gde Mertha (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
through the development of carbon zinc as an organic material produced from photosynthesis and stored and transported in the form of seagrass vegetation biomass. Seagrass is one of the aquatic vegetation that is able to absorb and store carbon. Seagrasses have the ability to absorb carbon through the process of photosynthesis. The purpose of this study was to describe the potential carbon content of seagrass species in the South Coastal Waters of East Lombok. This type of research is an expolarative descriptive research. The research method is a quadratic transect method. The population of this study were all seagrass species contained in 3 research stations. The collected data was then analyzed using analysis of seagrass species composition, seagrass cover, seagrass density, diversity, uniformity, dominance and analysis of carbon content through seagrass stand biomass (leaves, rhizomes/stems and roots). The result of this research is the discovery of 9 species of seagrass on Lungkak Beach and 5 species of seagrass on Gili Kere and Poton Bakau. The species density in the three study sites ranged from 0.09 to 56.91 stands/m2. Seagrass biomass values ranged from 1.47-261.9 gbk/m2 and total carbon content ranged from 295.91±202.88 gC. The value of this biomass and carbon content was dominated by seagrass species with large morphology such as Enhalus acroides, Thalasia hemprici, Cymodocea rotundata, and Cymodocea cerillata and high density and cover values of seagrass. The relationship between seagrass cover and seagrass carbon has a significant relationship where the higher the seagrass cover, the higher the carbon content of the seagrass.